Weed Detection in Perennial Ryegrass With Deep Learning Convolutional Neural Network - Yu, Jialin; Schumann, Arnold W.; Cao, Zhe; Sharpe, Shaun M.; Boyd, Nathan S. (Frontiers in Plant Science, 2019)
Spot-spraying herbicides can substantially reduce herbicide input and weed control cost in turfgrass management systems. However, manual spot-spraying in large turfgrass areas is impractical. In this work, several deep convolutional neural networks (DCNN) were constructed for detection of dandelion (Taraxacum officinale Web.), ground ivy (Glechoma hederacea L.), and spotted spurge (Euphorbia maculata L.) growing in perennial ryegrass. When the networks were trained using a dataset containing a total of 15486 negative (images contained perennial ryegrass with no target weeds) and 17600 positive images (images contained target weeds), VGGNet achieved high F1 scores (≥0.9278), with high recall values (≥0.9952) for detection of Euphorbia maculata, Glechoma hederacea, and Taraxacum officinale growing in perennial ryegrass. The F1 scores of AlexNet ranged from 0.8437 to 0.9418 and were generally lower than VGGNet at detecting Euphorbia maculata, Glechoma hederacea, and Taraxacum officinale. GoogleNet is not an effective DCNN at detecting these weed species mainly due to the low precision values. DetectNet is an effective DCNN and achieved high F1 scores (≥0.9843) in the testing datasets for detection of Taraxacum officinale growing in perennial ryegrass. Overall, the approach of training DCNN, particularly VGGNet and DetectNet, presents a clear path toward developing a machine vision-based decision system in smart sprayers for precision weed control in perennial ryegrass.